O-174 Formation of the international partnership on automatic occupation coding – call for partners and collaboration. (14th March 2023) - Ge, Calvin; Elias, Peter; Friesen, Melissa; Peters, Susan; Schierholz, Malte
Abstract : Introduction: Job coding is important for occupational epidemiology. Occupational classifications, such as the ILO's International Standard Classification of Occupations (ISCO), are often used in job-exposure matrices (JEMs) and other models for exposure assessment in population-based studies. In these studies, assignment of job codes is often performed manually. This work is labourious, costly, and limited in reliability. Tools for automatic assignment of job codes are available for select coding systems and languages; however, their application in occupational epidemiology is limited mainly due to uncertainties around tool performance and how their use might impact exposure assessment. Material and Methods: Following discussions held during and after EPICOH 2021, the International Partnership on Automatic Occupation Coding (IPAOC) was formed by a group of occupational exposure assessment scientists and epidemiologists. Aiming to promote knowledge sharing and collaborations on the development of automatic coding algorithms and software, IPAOC met regularly and actively sought new partners in 2022 while defining its research agenda. Results and Conclusions: As of November 2022, IPAOC includes more than 40 members from six countries. The partnership is diverse and multidisciplinary; research areas represented include computer and data science, labour economics, occupational medicine, occupational health, official statistics, statistics, and sociology. Member interests in automatic job coding also span across a number of languages and occupation classifications systems, including in English (Coding: ISCO, US SOC and Canadian NOC), French (PCS), German (KldB), and Dutch (ISCO). For 2023, IPAOC's goals are to address two main challenges for developing better automatic job coding tools: siloed development in separate projects/countries and low training data availability. Specifically, IPAOC will 1) apply for funding for a week-long workshop meeting to facilitate knowledge sharing and cooperation in the Lorentz Center in Leiden, the Netherlands; and 2) develop a shared benchmarking dataset for coding algorithm development.